The prognostic value of the Dandel's index in patients undergoing tricuspid transcatheter edge-to-edge repair - Kassar, Mohammad; Brugger, Nicolas; Stolz, Lukas; Gerçek, Muhammed; Fortmeier, Vera; Kresoja, Karl-Patrik; von Stein, Jennifer; Koell, Benedikt; Rottbauer, Wolfgang; Goebel, Bjoern; Denti, Paolo; Achouh, Paul; et al. (European journal of heart failure, 2024)
Aims Conventional parameters of right ventricular (RV) function are load-dependent and therefore do not accurately reflect contractility in patients with relevant tricuspid regurgitation (TR). RV adaptability to load has been characterized using the Dandel's index in patients with heart failure, but its prognostic value in patients undergoing tricuspid transcatheter edge-to-edge repair (T-TEER) has not been investigated so far. Methods and results From the EuroTR registry (2019 to 2022), patients with complete datasets and a minimum of 2-years of follow-up were included. RV functional parameters (i.e. tricuspid annular plane systolic excursion [TAPSE], fractional area change [FAC], TAPSE/systolic pulmonary arterial pressure [sPAP]), as well as a echocardiographic RV load adaptation index (Dandel's index) were assessed and their predictive value in terms of all-cause mortality evaluated using logistic multivariate logistic regression. The majority of the 364 patients had secondary TR (96%) and were severely symptomatic (New York Heart Association class ≥III; 92%). At 2-year follow-up, 36% of patients had died. Functional RV parameters (TAPSE: hazard ratio [HR] 0.72, 95% confidence interval [CI] 0.62-0.84; FAC: HR 0.73, 95% CI 0.59-0.91), coupling index (TAPSE/sPAP: HR 0.8, 95% CI 0.65-0.99) and Dandel's index (HR 0.67, 95% CI 0.53-0.85) were all associated with mortality at 2 years in univariable analyses. In a multivariate logistic regression model, the Dandel's index maintained its predictive value (p < 0.001), along with TAPSE and absence of signs of right heart failure, with an optimal threshold of 20.5 determined by the receiver-operating characteristic analysis. This threshold also successfully predicted cardiac hospital readmission. A multivariate analysis was conducted to identify parameters linked to RV function and predicting clinical outcomes. Conclusion Assessment of the RV capacity to adjust for changes in loading conditions predicted mortality in patients with severe symptomatic TR undergoing T-TEER. The use of a multiparametric approach including the Dandel's index to assess RV function had an incremental value for the stratification of patients into subgroups with different prognosis.